Axial Implants in Immediate Function for Partial Rehabilitation in the Maxilla and Mandible: A Retrospective Clinical Study Evaluating the Long-Term Outcome (Up to 10 Years). Issue 5 (October 2015) - Maló, Paulo; de Araújo Nobre, Miguel; Lopes, Armando; Queridinha, Bruno; Ferro, Ana; Gravito, Inês
Abstract : Background: There is a need of long-term studies evaluating the outcome of fixed partial rehabilitations (FPR) supported by implants in an immediate function protocol. The aim of this retrospective cohort study was to investigate the long-term outcome of FPR supported by implants placed in immediate function. Methods: One hundred ninety-nine patients were consecutively included, between 1998 and 2010, with 481 implants supporting 213 FPR (maxilla: 87 and mandible: 126). Primary outcome measures were implant and FPR survival rates; secondary outcome measures were marginal bone levels at 5 and 10 years and incidence of mechanical and biological complications. Results: The cumulative implant survival rate was 98.5% and 99.0% after 5 years and 92.7% and 96.7% after 10 years, using the patient and implant as unit of analysis, respectively. No prostheses were lost. Average (SD) marginal bone levels were 1.79 (0.93) and 1.89 mm (0.81 mm) at 5 and 10 years of follow-up. Mechanical complications occurred in 43 patients (21.6%), biological complications occurred in 12 patients (6%), and 16 implants (3.3%) up to the 10 years follow-up. Conclusions: FPR supported by immediate function implants in both jaws is a viable and safe treatment alternative.